TWO DIRECTIONS OF FORMATION OF SOLID SOLUTION OF ANHYDROUS COBALT(II) AND ZINC DIPHOSPHATES - Антрапцева, Надія; Фількін, Ігор; Біла, Галина (SWorldJournal, 2022)
The composition, temperature ranges of formation and thermal stability of the heat treatment products of a solid solution with the general formula Со2-хZnхP2O7·6H2O were determined. The cation nature effect on them was concretized. The end of h